The effect of age at school entry on college admission and earnings: A regression-discontinuity approach - Rafael Matta; Rafael P. Ribas; Breno Sampaio; Gustavo R. Sampaio (IZA Journal of Labor Economics, 2016)
This paper provides evidence of the effect of age at school entry on college admission and earnings. It does so by exploiting a number of features in the application process to one of the major flagship universities in Brazil. By comparing applicants with different ages at school entry depending on whether they were born on December 31 or on January 1, our estimates show that applicants who delayed first-grade enrollment present higher aptitude test scores and probability of admission. Our results further suggest that advantaged applicants also earn more early in their careers.
Keywords: I21; J24; 330; School starting age; School achievement; College admission; Aptitude test score